Migrant Remittance Practices among Hungarian Health Care Workers in Norway (Szociológiai Szemle, 2023)
Although current researches aim to reveal the migration potential and practice of emigration of Hungarian health professionals, little attention is paid on measurable and descriptive data of their migrant remittance practices. The aim of this study is to present the relating patterns of remittance flows, demonstrating the usage and outcomes of migrant transfers, and investments through the relating literature, drawing especially on Tharmalingham's typology. I conducted a qualitative inquiry by half-structured interviews with Hungarian physicians and nurses employed in Norway in order to analyze their migrant remittance practices according to their social status, network, and motivations. Based on the data, I conclude that migrant remittances have greater impact on social, and economic mobility of the beneficiary family of lower-middle class health professionals, as the narratives showed that they are willing to remit much more than migrants from higher social class. Family-oriented, individual remittances are the most common sorts that are frequently invested in services besides materialized use.